The AI marketing canvas : a five-stage road map to implementing artificial intelligence in marketing - Venkatesan, Rajkumar; Lecinski, Jim (Stanford Business Books, an imprint of Stanford University Press, 2021)
"This book offers a direct, actionable plan CMOs can use to map out initiatives that are properly sequenced and designed for success--regardless of where their marketing organization is in the process. The book is also a call to action for marketing leaders to confront and decide how they will address this critical pivot point in marketing. The authors pose to marketers the critical questions of (1) 'How should modern Marketers be thinking about Artificial Intelligence and Machine Learning?' and (2) 'How should Marketers be developing a strategy & plan to implement AI into their marketing toolkit?' Opening chapters provide marketing leaders with an overview of what exactly AI is, how is it different than traditional computer science approaches; then proposes a best practice 5 stage framework for how to implement what the authors term the 'AI Marketing Canvas.' This is based on research and interviews the authors did with leading Marketers, and offers many tangible examples of what brands are doing at each stage of the AI Marketing Canvas. By way of guidance, Venkatesan and Lecinski provide examples of brands currently, successfully, weaving AI into their marketing strategies, including Google, LYFT, Ancestry.com, and Coca-Cola. The book ends with a discussion of important implications for marketing leaders, for your team, people and culture. Strategically sound, application-focused, and customer-centric, this book fills a lacuna in actionable marketing strategy guidance at a time when it is most needed"--